Potential Role of Cellular Senescence in Asthma - Wang, Zhao-Ni; Su, Ruo-Nan; Yang, Bi-Yuan; Yang, Ke-Xin; Yang, Li-Fen; Yan, Yan; Chen, Zhuang-Gui (Frontiers in Cell and Developmental Biology, 2020)
Cellular senescence is a complicated process featured by irreversible cell cycle arrest and senescence-associated secreted phenotype (SASP), resulting in accumulation of senescent cells and low-grade inflammation. Cellular senescence not only occurs during the natural aging of normal cells, but also can be accelerated by various pathological factors. Cumulative studies have shown the role of cellular senescence in the pathogenesis of chronic lung diseases including chronic obstructive pulmonary diseases (COPD) and idiopathic pulmonary fibrosis (IPF) by promoting airway inflammation and airway remodeling. Recently, great interest has been raised in the involvement of cellular senescence in asthma. Limited but valuable data has indicated accelerating cellular senescence in asthma. This review will compile current findings regarding the underlying relationship between cellular senescence and asthma, mainly through discussing the potential mechanisms of cellular senescence in asthma, the impact of senescent cells on the pathobiology of asthma, and the efficiency and feasibility of using anti-aging therapies in asthmatic patients.